Pengembangan Fitur FIT Sebagai Teknologi Pengukur Pakaian Di E-Commerce - Angel Rich Faustine Winata; Elvinson Wijaya; Iven Marchellia; Kevin Tan; Yehezkiel Michael Sutara; Lifia Yola Febrianti (Jurnal Sains dan Teknologi, 2023)
This research aims to develop the design of the FIT feature. FIT is a feature integrated into e-commerce that is designed to provide accurate clothing sizes according to user needs. This feature is designed with the aim of reducing problems that occur when shopping for clothes online, such as sizing errors. This research method uses the Research and Development (R&D) method with the Thiagarajan model. Even so, this research only reached the design stage. The results of this research present the design of the FIT feature which is based on artificial intelligence and augmented reality technology to simulate real clothes purchased by users